Aretrospective evaluation of the intellectual structure of private agricultural and food standards research in global trade - Lwesya, Francis; Mbukwa, Justine N. (International Trade, Politics and Development, 2024)
Article published by International Trade, Politics and Development in Emerald Insight Vol. 7 No. 2, 2023, pp. 92-114